Analysis for Science Librarians of the 2016 Nobel Prize in Chemistry: Molecular Machines. Issue 1 (2nd January 2017) - Wrublewski, Donna T.
ABSTRACT: The 2016 Nobel Prize in Chemistry recognized three scientists for their contributions to exploiting molecules that can act as mechanical components in molecular machines. Jean-Pierre Sauvage was the first to demonstrate a new, simpler mechanism to synthesize catenanes—mechanically interlocked molecular rings. Sir Fraser Stoddart showed how rotaxanes—mechanically interlocked rings on molecular sticks—can be manipulated by external fields. Ben Feringa pioneered molecular rotors—molecules that have components that can rotate in one direction only. Each of these scientists has contributed a key piece to solving the challenge of building a molecular machine.